Occurrence of Aspergillus section Flavi and section Nigri and aflatoxins in raw cashew kernels (Anacardium occidentale L.) from Benin. (July 2016) - Lamboni, Yendouban; Frisvad, Jens C.; Hell, Kerstin; Linnemann, Anita R.; Nout, Rob M.J.; Tamo, Manuele; Nielsen, Kristian F.; van Boekel, Martinus A.J.S.; Smid, Eddy J.
Abstract: The objective of this study was to evaluate the presence of Aspergillus section Flavi and A . section Nigri in cashew nuts harvested in the Northern Guinea (NG) and Southern Sudanian (SS) agro-ecological zones of Benin. Also, the presence of aflatoxins was investigated. For detection of fungal contamination, a total of 100 kernels/sample (with disinfection) and 40 kernels/sample (without disinfection) were plated. Seventy samples from fourteen villages were used. Aflatoxins occurrence was analysed on 84 samples by ultra–high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). The average water content and the cashew nuts count were respectively 8.6% and 172 nuts/kg in NG and 8.7% and 174 nuts/kg in SS. Significant differences between villages in both zones were found for both water content and nuts count. In disinfected samples, strains of Aspergillus section Nigri were predominant, in NG and SS zones (90.2% and 87.2%) respectively. When non disinfected kernels were plated, A . section Nigri was predominant in both NG and SS zones, with percentages of 89.7% and 93.4%, respectively. None of the 84 nuts samples were positive for natural occurrence of aflatoxins with a detection limit of 0.05–0.2 μg/kg. Highlights: Water content and cashew nuts count were in the range of good quality for export. Cashew nuts were less contaminated by Aspergillus section Flavi compared to Nigri . No aflatoxins were detected in cashew nuts from Benin. Beninese cashew nuts were in the range of good quality for export.